Advent, origin and settlement of andrabi syeds in Kashmir - Ali, Damsaz (International Multidisciplinary Research Journal, 2011)
Among all nations and races who had come in contact with Kashmir none of them had left everlasting influences on the culture and civilization of the valley as Central Asian. Contacts with Central Asia were developed long before the political domination of Muslims. The foundation of Muslim rule opened the flood gates for the infiltration of Persian and Central Asian people in the valley. The Andrabi Syeds were also from Central Asia i.e. from Afghanistan (Andrab). They had influenced both the rulers and commoners equally.